Regression of multifocoal in transit melanoma metastases after palliative resection of dominant masses and 2 years after treatment with ipilimumab. Issue 1 (18th July 2017) - Moreira, Raphael B.; Hamieh, Lana; Gjini, Evisa; Lako, Ana; Krajewski, Katherine M.; Yoon, Charles H.; Ott, Patrick A.
Abstract : Background: Spontaneous regression of metastatic melanoma and delayed responses more than one year after treatment with ipilimumab are rarely seen. Case presentation: Here, we present the case of a patient with in transit metastases from cutaneous melanoma on his right lower extremity who achieved complete regression of all metastatic lesions 13 months after the first of two consecutive palliative resections of dominant masses and more than two years after treatment with ipilimumab. Conclusion: The exact cause of our patient's sudden onset of tumor regression remains speculative. We hypothesize that the operative trauma followed by the postoperative infections augmented an innate immune response.